In praise of megacities in a global world1. Issue 2 (2nd May 2013) - Kourtit, Karima; Nijkamp, Peter; Kourtit, Karima; Nijkamp, Peter; Partridge, Mark D.
Abstract This paper argues that in the historical evolution of cities, large‐scale urbanization is not only a fact, but a necessary outcome of the forces of globalization and competition. The current trend towards large cities and megacities in a complex global urban system, operating and interacting at a local to global multi‐layer scale, is inevitable. However, their dynamics is as yet a poorly understood phenomenon that deserves full‐scale policy action and research attention in our highly diversified space‐economy.